Pozzolanic activity of calcined halloysite-rich kaolinitic clays - Tironi, Alejandra (2017)
The aim of this study is to determine the pozzolanic activity of clays with high content of halloysite/kaolinite, and to evaluate the influence of halloysite/kaolinite ratio and halloysite morphology in the development of pozzolanic activity of the calcined clays. For this purpose, three different natural clays from Río Negro Province, Argentine, were selected and completely characterized. After calcined at 700 °C and ground to 80% of particle size < 45 μm, pozzolanic activity was determined using the electrical conductivity test, the Frattini test and the compressive strength index. Results show that all calcined clays are classified as high reactive pozzolana. The presence of kaolinite and spheroidal halloysite exerts great influence at early ages; while tubular halloysite has greater influence in the pozzolanic activity and the compressive strength of mortars at later ages.